How to submit an article online to the OBJN and discover the pleasure of publishing. - Isabel C.F. da Cruz (Online Brazilian Journal of Nursing, 2005)
OBJN welcomes authors who would like to develop the nursing and the health care science. This text will assist you in submiting an manuscript online.